2019
DOI: 10.3390/nano9050798
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Engineering of Graphene Nanosheets at MgO Particles for Thermal Conductivity Enhancement of Polymer Composites

Abstract: An important task in facilitating the development of thermally conducting graphene/polymer nanocomposites is to suppress the intrinsically strong intersheet π-π stacking of graphene, and thereby to improve the exfoliation and dispersion of graphene in the matrix. Here, a pre-programmed intercalation approach to realize the in situ growth of graphene nanosheets at the inorganic template is demonstrated. Specifically, microsized MgO granules with controlled geometrical size were synthesized using a precipitation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…He, G [2] quantitatively demonstrated that pGNPs@Ag reduces the ITR, which contributes to the improving of the composite k. Lin C et al [3] doped nano-TATB particles into PBX to construct a novel self-reinforced PBX, which significantly improved the strength and toughness. Pan L et al [4] established a constitutive relationship between graphene microstructure and thermal conductivity of PBX. Pietrak, K considered the case where interfacial thermal resistance is present in the heat transfer model [5].…”
Section: Introductionmentioning
confidence: 99%
“…He, G [2] quantitatively demonstrated that pGNPs@Ag reduces the ITR, which contributes to the improving of the composite k. Lin C et al [3] doped nano-TATB particles into PBX to construct a novel self-reinforced PBX, which significantly improved the strength and toughness. Pan L et al [4] established a constitutive relationship between graphene microstructure and thermal conductivity of PBX. Pietrak, K considered the case where interfacial thermal resistance is present in the heat transfer model [5].…”
Section: Introductionmentioning
confidence: 99%
“…To enhance interfacial inter‐linkage with the polymer matrix, GO sheets are chemically modified with functionalization agents 15–18 . Some studies have shown that antibacterial effects of GO/rGO are detected at concentrations higher than 4 g/mL, which is considered the maximum concentration that is not cytotoxic 19,20 . Since in the preparation of nanocomposites, the desired properties can be achieved at a low percentage of reinforcement, the graphene‐based nanocomposites show low toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18] Some studies have shown that antibacterial effects of GO/rGO are detected at concentrations higher than 4 g/mL, which is considered the maximum concentration that is not cytotoxic. 19,20 Since in the preparation of nanocomposites, the desired properties can be achieved at a low percentage of reinforcement, the graphene-based nanocomposites show low toxicity. This study will use bio-based diol, L-Alanine, and curcumin to synthesize a biodegradable poly(ester-imide) (PEI) with excellent mechanical and thermal properties.…”
mentioning
confidence: 99%
“…15,16 Therefore, it is important to improve the compatibility between GO and the matrix. For example, silane coupling agents 10,17 and inorganic nanoparticles 18 have been used to enhance the GO dispersion and compatibility in the polymer matrix. It was reported that a graphene nanoplatelet covalently functionalized 3-aminopropyltriethoxysilane/boron phenolic resin composite (K-Gnp/BPR) was prepared.…”
Section: Introductionmentioning
confidence: 99%